DEVELOPMENT OF PROFESSIONAL-PEDAGOGICAL COMPETENCE IN FUTURE IT TEACHERS IN THE INTEGRATION OF HUMANITARIAN AND NATURAL-SCIENTIFIC, GENERAL PROFESSIONAL COURSES - Sh. U. Usmankulov (Scholar Express Journal, 2022)
The article discusses the purpose of integration, vertical integration, horizontal integration, ways of developing the professional and pedagogical competence of future computer science teachers, the application of SIAM2P education with the transfer of STEAM principles to professional pedagogical activities, the advantages of SIAM2P education, as well as the humanities and natural sciences. A table is provided with course titles and related topics selected for the integrative approach
Keywords: integration; goal of integration; vertical integration,; horizontal integration